NoSqlayer: a Framework for Migrating Relational Datasets to NoSQL Models - Vale, Fernando; Rocha, Leonardo (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2014)
In software development, migration from a Data Base Management System (DBMS) to another with distinct characteristics, is a challenge for programmers and database administrators. Changes in the application code in order to comply with new DBMS are vast and may causing migrations infeasible. In this work we present NoSQLayer, a framework that supports migrating from relational to NoSQL DBMS. This framework is divided in two parts: (1) migration module, that perform the migration between DBMSs and (2) mapping module, that is a persistence layer to process database requests. Experiments show NoSQLayer as a handful solution suitable to handle large volume of data.